Barrett's oesophagus: epidemiology, diagnosis and clinical management. Issue 7 (3rd October 2016) - Whiteman, David C; Kendall, Bradley J
Summary: Barrett's oesophagus is a condition characterised by partial replacement of the normal squamous epithelium of the lower oesophagus by a metaplastic columnar epithelium containing goblet cells (intestinal metaplasia). Barrett's oesophagus is important clinically because those afflicted are predisposed to oesophageal adenocarcinoma. Prevalence surveys suggest that up to 2% of the population may be affected; most will be unaware of their diagnosis. Risk factors include age, male sex, gastro‐oesophageal acid reflux, central obesity and smoking. Helicobacter pylori infection confers a reduced risk of Barrett's oesophagus. Risks of cancer progression are lower than originally reported and are now estimated at 1–3 per 1000 patient‐years for patients with non‐dysplastic Barrett's oesophagus. Progression rates are higher for patients with long segment (≥ 3 cm) and dysplastic Barrett's oesophagus. Australian guidelines have been developed to aid practitioners in managing patients with Barrett's oesophagus and early oesophageal adenocarcinoma. While generalised population screening for Barrett's oesophagus is not recommended, endoscopic surveillance of patients with confirmed Barrett's oesophagus is recommended, with surveillance intervals dependent on segment length and presence of dysplasia. New techniques such as endoscopic mucosal resection and endoscopic radiofrequency ablation are now available to treat patients with dysplasia and early oesophageal adenocarcinoma. New screening and surveillance technologies are currently under investigation; these may prove cost‐effective in identifying and managing patients in the community.